On-Chip Copper-Based vs. Optical Interconnects: Delay Uncertainty, Latency, Power, and Bandwidth Density Comparative Predictions - Guoqing Chen; Hui Chen; Haurylau, M.; Nelson, N.A.; Albonesi, D.H.; Fauchet, P.M.; Friedman, E.G. (2006 International Interconnect Technology Conference, 2006)
As CMOS technology is scaled, it has become increasingly difficult for conventional copper interconnect to satisfy different design requirements. On-chip optical interconnect has been considered as a potential substitute for electrical interconnect. In this paper, predictions of the performance of CMOS compatible optical devices are made based on current state-of-art optical technologies. Based on these predictions, electrical and optical interconnects are compared for delay uncertainty, latency, power, and bandwidth density